(untitled) (Biological Sciences - PJSIR, 2004)
The importance of pyrolysis of preceramic organometallic compounds is increasing year by year as a key technology for the synthesis of new inorganic materials. According to this process, preceramic polymers are synthesized from monomer units. After cross-linking of such precursors, the obtained preceramic networks are transformed by pyrolysis into amor- phous materials. Further increase of the temperature yields thermodynamically stable crystalline materials. In this paper, the general methods of the synthesis of ceramic materials based on the Si-B-C-N system via thermolysis of preceramic compounds have been reviewed. Bulk materials, coatings and fibers of such materials reveal quite interesting high tempera- ture properties.